The Impact of Fiscal Incentives on Total Cost of Electrified Vehicle Ownership in Indonesia - Riyanto Riyanto (Jurnal Ekonomi dan Studi Pembangunan, 2025)
The Indonesian government has provided fiscal incentives to develop a battery electric vehicle (BEV) market, such as luxury goods tax (PPnBM) exemptions, vehicle title transfer fee (BBNKB) reduction, and motor vehicle tax (PKB) reduction for BEV users. With several fiscal incentives, BEV prices are expected to compete with Internal Combustion Engine Vehicle (ICEVs), thus consumers will switch to buying and using BEVs. Consumers, however, do not solely consider the price of BEVs; they also consider the total cost of ownership (TCO). In that regard, this study aims to construct a TCO model and calculate the total cost of ownership of Electrified Vehicles (x-EVs) and ICEVs. This study also attempts to analyze the impact of various fiscal incentives on the TCO of BEV. The result of this study shows that (1) without any fiscal incentives, the amount of x-EV’s TCO (Total Cost of Ownership) is comparably higher than that of ICEV; (2) PHEV’s and HEV’s TCOs are lower than the TCO of ICEV with the provision of PPnBM-free incentives and PPnBM reduction respectively; and (3) three fiscal incentives (PPnBM exemption and BBNKB and PKB discount) are urgently required to lower the TCO of BEV and penetrate the Indonesian market.